CONTRASTIVE ANALYSIS OF PHRASES WITH THE CONCEPT “STUDENT” IN ENGLISH AND UZBEK LANGUAGES - Narmuratov Zayniddin Radjabovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
This article presents a contrastive linguistic and cultural analysis of phrases and expressions related to the concept “student” in English and Uzbek languages. The study focuses on identifying similarities and differences in the semantic, structural, and cultural representations of the term in both linguistic systems. The findings reveal that English emphasizes individuality, creativity, and practical learning, while Uzbek reflects values of respect, discipline, and moral responsibility in the educational process. The article highlights how cultural perspectives shape language use related to students and education.